HUBUNGAN TINDAKAN PHBS DENGAN PENCEGAHAN DIARE PADA ANAK SD NEGERI 2 TATAARAN TONDANO KABUPATEN MINAHASA - Timah, Stefanus; Yigibolom, Mepry (Journal Of Community & Emergency, 2024)
Health Promotion in educational institutions (Health Promoting School) launched by the World Health Organization, uses a holistic model that includes the relationship between physical, mental, social, and environmental aspects. This concept involves the role of health workers by encouraging their participation in increasing the knowledge and skills of students (starting from an early age) about health and showing the meaning of the environment as a contributor to children's health such as the physical condition of schools, clean water sanitation, and play environments. Healthy (PHBS) is part of the government's efforts through preventive health services. Preventive health service is an activity to prevent a health problem/disease. Research Objectives To know the relationship between Clean and Healthy Lifestyle and Diarrhea Prevention in State Elementary School 2 Tataaran Tondano. The type of research is quantitative descriptive with a cross-sectional study approach, the research time is in November 2021 and the research location is at the State Elementary School 2 Tataaran Tondano. The statistical test used is the Chi-Square Test with a 95% confidence level if . The results showed that the results of the test using the chi square test had a p value of 0.001 so there was a relationship between Clean and Healthy Life Behavior and Prevention of Diarrhea in State Elementary School Students 2 Tataaran Tondano, Minahasa Regency. T The conclusion in this study is that the behavior of clean and healthy life in State Elementary School 2 Tataaran Tondano is more good than less good. Prevention of Diarrhea in State Elementary School Students 2 Tataaran Tondano has mostly carried out Diarrhea Prevention. The suggestion in this research is that this research is to be a reference for further researchers in conducting more in-depth research on Clean and Healthy Life Behavior with other variables related to Environmental Hygiene <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">